Inhibitors of Factor XIII/13 in Older Patients - Ichinose, Akitada; for the The Japanese Collaborative Research Group (JCRG) on AH13 Hemorrhagic Acquired Coagulopathies (Seminars in Thrombosis and Hemostasis, 2014)
Factor XIII/13 (FXIII or F13) is a plasma protransglutaminase, which stabilizes fibrin clots, and thus plays an important role in hemostasis. Autoimmune hemo(rrha)philia due to anti-F13 autoantibodies (AH13) has been on the rise in Japan, which has become the leading superaging society in the 21st century. The mean age of Japanese AH13 cases has risen to 70.4 years. A total of 83 AH13 cases have been diagnosed in the world as of July 2014. To raise the awareness of AH13, the author and members of the Japanese Collaborative Research Group first proposed “Criterion and Algorithm of Laboratory Tests for anti F13” in February 2012. AH13 is not just an acquired isolated defect of F13 molecule itself but a disturbance caused by autoantibodies. Accordingly, AH13 cases are diagnosed in patients with otherwise unexplained hemorrhages by a combination of a severe deficiency of F13 activity and the presence of anti-F13 autoantibodies. As patients with this disease manifest life-threatening bleeding symptoms, prompt diagnosis and proper treatment are essential. Because AH13 tends to become chronic and intractable, affected patients must be closely followed for a prolonged period.
Keywords: anti-factor XIII/13 autoantibody; autoimmune hemorrhagic disease; chronic intractable disease; hemostatic therapy; immunosuppressive treatment